Výhovorka - Lopašovská, Milka; Janovic, Tomáš, 1937-2023; Škreko, Benjamín; Zimka, Ondrej (Košice : Východoslovenské vydavateľstvo, 1987)
Výber humoristických poviedok.
Keywords: slovenská literatúra; humoristické poviedky; starší školský vek